Treatment of in-stent restenosis with excimer laser coronary angioplasty - Karaca, I; Ilkay, E; Akbulut, M; Yavuzkir, M (Int Heart Journal Assoc, 2003)
Diffuse in-stent restenosis remains an important problem in percutaneous transluminal coronary angioplasty (PTCA). In this trial, we-studied the early and mid-term outcomes of excimer laser coronary angioplasty (ELCA) on diffuse in-stent restenosis. ELCA was performed in 23 patients (19 males). The mean length of the lesions was 14.3 +/- 3 mm and the mean age was 58 7 years. The minimal lumen diameter (MLD) was measured by on-line quantitative coronary angiography. Before the procedure, MLD was 0.9 +/- 0.4. The Q/non-Q-wave myocardial infarction (MI), coronary artery bypass graft (CABG), PTCA, and mortality were recorded during the procedure and at 6 months follow up. The fluence of laser emission was 45 mj/m(2) and the repetition rate was 25 pulses per second. Adjunctive balloon angioplasty was performed in all of the cases at a mean 7 2 atm pressure. The procedure was successfully performed in all of the cases. Type-B dissection developed. after ELCA in I patient (4%). Perforation, death, cerebrovascular accidents, emergency CABG, PTCA or Q/non-Q wave myocardial infarction were not observed. MLD was 0.9 +/- 0.4 mm before ELCA, 1.8 +/- 0.9 mm (P<0.05) after ELCA, and 3.1 +/- 0.7mm after PTCA. At 6months follow up, there were 2 (8.7%) Q-wave myocardial infarctions and 2 (8.7%) recurrent anginal pain cases. Control angiography was obtained in 20 cases (87%). Control angiography was not accepted by 3 patients. Their maximal exercise test was negative. Angiographic restenosis was observed in 6 cases (30%). The rate of target lesion revascularization (TLR) was 5 of 23 (22%) in the patients treated with ELCA. It is concluded, ELCA is a safe and efficient debulking technology for treating diffuse in-stent restenosis.
Keywords: in-stent restenosis; laser; target lesion revascularization (TLR)